A Population-Based Analysis of Survival for Sinonasal Rhabdomyosarcoma. (July 2017) - Unsal, Aykut A.; Chung, Sei Yeon; Unsal, Aylin B.; Baredes, Soly; Eloy, Jean Anderson
Objectives: Literature detailing factors affecting survival in sinonasal rhabdomyosarcoma (SNRMS) is limited due to its rarity. We analyze the demographics, potential prognostic factors, overall survival, and treatment efficacy of SNRMS. Study Design and Setting: Administrative database study. Methods: SNRMS was queried in the SEER database (1973-2013; Surveillance, Epidemiology, and End Results). Data were analyzed for demographic and clinicopathologic trends. Kaplan-Meier model was utilized for assessing survival. Results: A total of 286 cases of SNRMS were identified. The median age at diagnosis was 24.5 years, and the mean tumor size was 5.1 cm. Overall 5-, 10-, and 20-year disease-specific survival was 35.1%, 25.4%, and 12.0%, respectively. Regional lymph node involvement was present at diagnosis in more than half of cases (54.3%) and distant metastasis in 32.2% of cases. Alveolar rhabdomyosarcoma (54.9%) and embryonal rhabdomyosarcoma (23.8%) were the primary histologies. Alveolar-type SNRMS was more likely than the embryonal type to metastasize to distant sites (41.7% vs 24.1%), and it possessed poorer 5-year survival (29.2% vs 45.6%). Distant metastasis decreased 5-year survival from 35.1% to 3.8%, whereas lymph node involvement did not significantly affect survival. Patients <10 years old had the highest survival rates. Primary tumor origin by subsite did not significantly affect survival. Smaller tumor sizes and earlier Intergroup Rhabdomyosarcoma Study Group stages were associated with improved outcomes. Surgical therapy had the highest survival rates. Conclusion: SNRMS has overall poorer prognosis than all other parameningeal rhabdomyosarcomas studied. Age <10 years, smaller tumor sizes, lack of distant metastasis, localized tumors, earlier Intergroup Rhabdomyosarcoma Study Group stages, and embryonal histology were all associated with improved outcomes.